2008
DOI: 10.1016/j.cell.2008.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Early Sexual Origins of Homeoprotein Heterodimerization and Evolution of the Plant KNOX/BELL Family

Abstract: Developmental mechanisms that yield multicellular diversity are proving to be well conserved within lineages, generating interest in their origins in unicellular ancestors. We report that molecular regulation of the haploid-diploid transition in Chlamydomonas, a unicellular green soil alga, shares common ancestry with differentiation pathways in land plants. Two homeoproteins, Gsp1 and Gsm1, contributed by gametes of plus and minus mating types respectively, physically interact and translocate from the cytosol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
248
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(258 citation statements)
references
References 73 publications
8
248
1
1
Order By: Relevance
“…Regarding the genetic mechanism underlying the full program of zygote development, GSP1 originating from plus gametes and GSM1 originating from minus gametes both contribute to zygote development, including the resorption of flagella, fusion of nuclei and chloroplasts, destruction of minus gamete G-chloroplast DNA, and secretion of a resistant cell wall (Wilson et al 1999). Earlier studies showed that the ectopic expression of GSP1 in minus gametes or of GSM1 in plus gametes can switch the zygotic differentiation programme on, and the resulting zygotes could undergo a normal meiosis (Zhao et al 2001, Lee et al 2008. Further research has uncovered the functional homology between GSP1/GSM1 and KNOX/BELL, which regulate stem-cell specification in land plants (Lee et al 2008).…”
Section: A Molecular Perspective On Fertility Genetic Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the genetic mechanism underlying the full program of zygote development, GSP1 originating from plus gametes and GSM1 originating from minus gametes both contribute to zygote development, including the resorption of flagella, fusion of nuclei and chloroplasts, destruction of minus gamete G-chloroplast DNA, and secretion of a resistant cell wall (Wilson et al 1999). Earlier studies showed that the ectopic expression of GSP1 in minus gametes or of GSM1 in plus gametes can switch the zygotic differentiation programme on, and the resulting zygotes could undergo a normal meiosis (Zhao et al 2001, Lee et al 2008. Further research has uncovered the functional homology between GSP1/GSM1 and KNOX/BELL, which regulate stem-cell specification in land plants (Lee et al 2008).…”
Section: A Molecular Perspective On Fertility Genetic Controlmentioning
confidence: 99%
“…Earlier studies showed that the ectopic expression of GSP1 in minus gametes or of GSM1 in plus gametes can switch the zygotic differentiation programme on, and the resulting zygotes could undergo a normal meiosis (Zhao et al 2001, Lee et al 2008. Further research has uncovered the functional homology between GSP1/GSM1 and KNOX/BELL, which regulate stem-cell specification in land plants (Lee et al 2008). Both genes are conserved among algae, although they appear to be lost in some lineages (Trebouxiophyceae, Gonium, Chondrus and Saccharina, see Supplemental Table S1).…”
Section: A Molecular Perspective On Fertility Genetic Controlmentioning
confidence: 99%
“…Interestingly, the genetic program that directs sporophyte development in the bryophyte moss Physcomitrella is directed by a KNOX family homeodomain transcription factor whose homologs in the chlorophyte alga C. reinhardtii direct development of the dormant diploid zygospore formed after fertilization (Lee et al 2008;Nishimura et al 2012;Sakakibara et al 2013). The role of these homeodomain proteins in charophyte algae has not been examined, but they are predicted to participate in zygote development.…”
Section: Multicellular Innovations In Land Plants That May Be Rooted mentioning
confidence: 99%
“…Indeed, combinatorial homeodomainbased transcriptional control of reproduction has deep phylogenetic roots. Ectopic expression of the homeoproteins Gsp1 and Gsm1 in the plus and minus strains of the unicellular green alga Chlamydomonas activates vegetative cells to form zygote-like structures (Lee et al 2008). Gsp1 and Gsp2 are members of the TALE (three amino acid loop extension) homeodomain containing transcription factors, which includes the class 1 KNOX and class 2 KNOX proteins.…”
Section: Phylogenetic Development Of the Embryophyte Life Cyclementioning
confidence: 99%